FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN SISWA DI SMK NEGERI KELOMPOK BISNIS DAN MANAJEMEN SEKABUPATEN KEBUMEN TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Factors which Influence Student’s Satisfaction of Vocational High Schools of Business and Management Groups in Kebumen Regency in the 2013/2014 Academic Year. This research aimed to know : (1) The influence of teacher’s abilities in classroom managements, learning facilities, and extracurricular activities simultaneously upon the student’s satisfaction of Vocational High Schools of Business and Management Groups in Kebumen Regency. (2) The influence of teacher’s skills in managing classroom upon the student’s satisfaction of Vocational High Schools students. (3) The influence of learning facilities upon the student’s satisfaction of Vocational High Schools, and (4) TheInfluence of extracurricular activities upon the student’s satisfaction of Vocational High Schools.This research was conducted in the State Vocational High School of Business and Management Groups, they were SMK Negeri 1 Kebumen, SMK Negeri 1 Karanganyar Kebumen, and SMK Negeri 1 Ambal Kebumen. The populations of this research were Vocational High School students of Business and Management groups by using sampling technique of Proportionate Stratified Random Sampling. The methods of data collections used questionnaires and documentations. The data analyzes used Multiple Regression. Based on the result of the research it can be concluded that: (1) There is a significant positive influence of teacher’s abilities in classroom managements, learning facilities, and extracurricular activities simultaneously upon the student’s satisfaction of Vocational High School of Business and Management Groups in Kebumen Regency. (2) There is a significant positive influence of the variable of teachers abilities in classroom managements upon the student’s satisfaction of Vocational High School of Business and Management Groups in Kebumen Regency. (3) There is a significant positive influence of the learning facilities variable upon the student’s satisfaction of Vocational High School of Business and Management Groups in Kebumen Regency. (4) There is a significant positive influence of the extracurricular activities variable upon the student’s satisfactionof Vocational High School of Business and Management Groups in Kebumen Regency.